A fair non-collateral consensus protocol based on Merkle tree for hierarchical IoT blockchain - Seyedeh Somayeh Fateminasab; Davoud Bahrepour; Seyed Reza Kamel Tabbakh (Scientific Reports)
Abstract In recent years, there has been a growing interest among researchers in Internet of Things Blockchain (IoTB). A critical aspect of IoTB is its consensus protocol, which faces challenges such as limited bandwidth, energy constraints, and storage space restrictions. To tackle these challenges, Hierarchical IoTB (HIoTB) networks have been proposed. However, determining the fair priority of block transactions and the trustworthiness of nodes remain two major open problems in the consensus protocols. This paper proposes a fair non-collateral consensus protocol named Proof of Action (PoAct), which utilizes Merkle tree-based techniques to address scalability, lightweightness, and energy efficiency in HIoTB. In the HIoTB network, we first determine the trustworthiness of nodes based on their computational resources verified through a Merkle tree proof. Then, relying on the proposed proof, we present a fair solution for selecting transactions to be included in a block, and assign a voting score to trustworthy nodes. We evaluate our proposed PoAct through various scenarios, demonstrating significant enhancements in throughput and execution time compared to puzzle-solving-based consensus protocols. Additionally, we argue that our proposed consensus protocol is scalable and energy-aware, thereby mitigating consensus attacks such as Sybil, Eclipse, and 51%, as well as addressing Fork occurrences issues.